5 MAIN CHARACTERISTICS OF CREATIVE PEOPLE - SEE IF YOU HAVE ANY OF THOSE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Often we heard, creativity is intelligence having fun (and often too that we heard this being associated to the famous Albert Einstein). Under common perception, we see creative people as gifted children that have been blessed with such talent towards solving grand challenges in life. We dubbed them as game changers and at times, envied by others.